Effects of exergames on mood and cognition in healthy older adults: A randomized pilot study - Moret, Beatrice; Nucci, Massimo; Campana, Gianluca (Frontiers in Psychology, 2022)
The elderly population is increasing and the implementation of stimulating training to promote active aging has become a research issue. This study aimed at investigating the effects of a cognitive-motor exergame training on cognitive functions and mood, in healthy older adults. A randomized controlled pilot study was conducted to compare a cognitive-motor exergame training with a passive control group. The training consisted of 8 sessions of 45 min each, including 10 interactive activities focused on several cognitive functions such as memory, processing speed and executive functions, all requiring motor planning and execution. A total of 57 participants were administered a battery of cognitive tests before and after the training. A mixed-effect ANOVA with group (experimental vs. control) as between factor and time (pre-and post-test) as within factor, was performed to evaluate the effect of the exergame training on cognitive abilities and mood. Results showed significant interaction effects in processing speed [STROOPC: F (1,53.4) = 9.04, p = 0.004, R2 = 0.82], inhibition [3backs’ false alarms: F (1,47.5) = 5.5, p = 0.02, R2 = 0.79], and mood [Beck Depression Inventory: F (1,55) = 4.15, p = 0.04, R2 = 0.6]. Even though post-hoc analyses did not provide statistical evidence supporting the interactions, overall data showed a trend toward better scores only for the experimental group, suggesting a potential improvement in information processing speed, working memory and mood. Exergaming may be a motivating and enjoyable approach to healthy and active aging.